Issues facing sugar beet and cane growers in the next round of WTO negotiations. - KING, David (1997)
Identifies the challenges for the WTO when it re-opens negotiations in 1999-2000 as: (1) to consolidate the results of the Uruguay Round; (2) to make new rules in areas such as foreign direct investment, competition policy and export credits; and (3) to address three general concerns, viz: (a) to make sure that trade liberalisation contributes to the elimination of poverty; (b) to make sure that regional free trade agreements are in conformity with WTO rules; (c) to integrate new partners into WTO, such as Russia and China.